(untitled) - أحمد, دلير عبدالله; علي, گەشە عبدالله (Sulaimani Journal for Humanities, 2021)
This research entitled (The tenses of the Verb in the Poems of Shawqiyat) by Ahmed Shawqi is a semantic study of the verb, which is one of the pillars of the actual sentence in the Arabic language, and we focused in it on its tenses within the context, have been illustrated as descriptive analysis. This research is an attempt to link grammatical tense with literature. The research is comprised of an introduction, theoretical frame and three parts. In the introduction, we talk about the semantic of the verb and its divisions. In the first part, the tenses of the past verb, have been explained. The second part is concerned with, the tenses of the present verb. The third part is about the tenses of the imperative. Finally, the most important results have been displayed, including that modern divisions of the verb tense can be applied to poetry preceded those divisions.